Bridging the Research Gap between Live Collections in Zoos and Preserved Collections in Natural History Museums. (21st April 2022) - Poo, Sinlan; Whitfield, Steven M; Shepack, Alexander; Watkins-Colwell, Gregory J; Nelson, Gil; Goodwin, Jillian; Bogisich, Allison; Brennan, Patricia L R; D'Agostino, Jennifer; Koo, Michelle S; Mendelson, Joseph R; Snyder, Rebecca; et al.
Abstract: Zoos and natural history museums are both collections-based institutions with important missions in biodiversity research and education. Animals in zoos are a repository and living record of the world's biodiversity, whereas natural history museums are a permanent historical record of snapshots of biodiversity in time. Surprisingly, despite significant overlap in institutional missions, formal partnerships between these institution types are infrequent. Life history information, pedigrees, and medical records maintained at zoos should be seen as complementary to historical records of morphology, genetics, and distribution kept at museums. Through examining both institution types, we synthesize the benefits and challenges of cross-institutional exchanges and propose actions to increase the dialog between zoos and museums. With a growing recognition of the importance of collections to the advancement of scientific research and discovery, a transformational impact could be made with long-term investments in connecting the institutions that are caretakers of living and preserved animals.